2017
DOI: 10.1007/s15010-017-1060-x
|View full text |Cite
|
Sign up to set email alerts
|

A 38-year-old woman with necrotising cervical lymphadenitis due to Histoplasma capsulatum

Abstract: Case presentationWe analysed a 38-year-old woman with disseminated histoplasmosis for primary immunodeficiency. Her blood showed no IFN-γ response while her peripheral blood mononuclear cells (PBMCs) did. We identified IFN-γ autoantibodies of the IgG class in her serum.Conclusion IFN-γ autoantibodies leading to infections were so far mainly detected in people from Asian descent, where it was found to be associated with certain HLA types. This may be the first patient of African descent, and without the typical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 22 publications
1
13
0
Order By: Relevance
“…Other opportunistic infections developed within 1 year after occurrence of disseminated NTM infection. 4 One patient had pulmonary tuberculosis, the other patient had tuberculosis pleurisy.…”
Section: Discussionmentioning
confidence: 99%
“…Other opportunistic infections developed within 1 year after occurrence of disseminated NTM infection. 4 One patient had pulmonary tuberculosis, the other patient had tuberculosis pleurisy.…”
Section: Discussionmentioning
confidence: 99%
“…The patient was previously treated for an angioimmunoblastic T-cell lymphoma with complete remission [13]. Van de Vosse et al [14] reported nAIFNG in a 38–year-old women of African descent, who presented with necrotizing lymphadenitis due to Histoplasma capsulatum . Her HLA haplotype did not overlap with the one found to be associated with AIGA [10,14].…”
Section: Autoantibodies To Ifn-γ Cause Susceptibility To Opportunistimentioning
confidence: 99%
“…Van de Vosse et al [14] reported nAIFNG in a 38–year-old women of African descent, who presented with necrotizing lymphadenitis due to Histoplasma capsulatum . Her HLA haplotype did not overlap with the one found to be associated with AIGA [10,14]. Miyashita et al [15] describe nAIGA associated disseminated M. avium infection presenting as bladder lesions and sterile pyuria in a 63-year-old Japanese women.…”
Section: Autoantibodies To Ifn-γ Cause Susceptibility To Opportunistimentioning
confidence: 99%
“…3234 However, opportunistic pathogenic infections have been reported in Caucasian patients with anti-IFN-γ AAbs living in the UK, USA, Germany as well as in patients of African ancestry. 16,19,20,35 Although correlations between anti-IFN-γ AAbs, types of opportunistic infections, clinical manifestations, HLA alleles, and ethnicity have been demonstrated, other issues, such as environmental factors and genetic diversity must be elucidated for in-depth understanding of this disease. Interestingly, by fitting a linear mixed model adjusted for age, sex, as well as the presence of infection, antibiotic use and cyclophosphamide or rituximab use, anti-IFN-γ AAbs levels decreased overtime regardless of ethnicity, even in the absence of immunomodulatory therapy.…”
Section: Anti-ifn-γ Aabs and Pathologymentioning
confidence: 99%